ANALISIS PENGARUH PROMOSI, HARGA DAN KEUNGGULAN PRODUK TERHADAP KINERJA PEMASARAN - Wartini, Sri (PRESTASI, 2013)
Marketing performance is influenced by various factors including the promotion, pricing and product excellence. The problem in this study is whether the promotion, pricing and product excellence have an influence on the performance of marketing either partially or simultaneously. The populations in this study are all consumers Honda Vario PT. Zirang Utama Prima, a total of 93 people. Analysis technique of the data used is the description of the analysis, multiple regression analysis and coefficient of determination.The results obtained tcount = 2.896, with sigcount = 0.000 which means the price is significantly affect the performance of marketing. Variable product excellence (X3) values obtained tcount = 7.517, with sigcount = 0.000 which means the benefits of product significantly influence the performance of marketing. Fcount obtained simultaneously = 48.536, sig= 0.000 with a means of promotion, pricing, and product excellence and significant simultaneous effect on the performance of marketing.The conclusions from this research that there are positive and significant effect either partially or simultaneously variable promotion, pricing and product excellence of the performance of product marketing at Honda Vario of PT. Prima Zirang Utama. The suggestion that can be given is the best PT. Prima Zirang Utama give discounts to consumers who buy in cash, to extend the repayment time and provides a choice of design, model, the colour to suit the needs of consumers.Key words: Promotion, Price, Product Excellence, Performance Marketing